An Ecofriendly and Stability-Indicating HPLC Method for Determination of Permethrin Isomers: Application to Pharmaceutical Analysis - Minoo Afshar; Niloufar Salkhordeh; Mehdi Rajabi (Journal of Chemistry)
A green, simple, and stability-indicating RP-HPLC method was developed for simultaneous determination of permethrin isomers in pharmaceutical preparations. The separation was based on a C18 analytical column (150 × 4.6 mm, i.d., 5 μm). The mobile phase consisted of ethanol: phosphoric acid solution (pH = 3) (67 : 33, v/v). The elution was carried out at 30°C temperature with a flow rate of 1.0 mL/min. Quantitation was achieved with UV detection at 215 nm. In forced degradation studies, the drug was subjected to oxidation, hydrolysis, photolysis, and heat. The method was validated for specificity, linearity, precision, accuracy, and robustness. The applied procedure was found to be linear in permethrin concentration range of 0.5–50 μg/mL with correlation coefficients of 0.9996 for each isomer. Precision was evaluated by replicate analysis in which % relative standard deviation (RSD) values for areas were found below 2.0. The recoveries obtained (99.24%–100.72%) ensured the accuracy of the developed method. The peaks of permethrin isomers well resolved from various degradation products as well as the pharmaceutical excipients. Accordingly, the proposed validated and sustainable procedure was proved to be proper for routine analyzing and stability studies of permethrin in pharmaceutical preparations.